USE OF MOLYBDENUM AS A STRUCTURAL MATERIAL OF FUEL ELEMENTS IN LEAD OR LEAD-BISMUTH EUTECTIC COOLED FAST REACTOR TO IMPROVE ITS SAFETY - B.K. Kozhakhmet; G.G. Kulikov; G.S. Nurbakova; S.B. Rustembayeva (Academic Scientific Journal of Computer Science, 2019)
In our previous works has been described that the mean prompt neutron lifetime in fast reactors can be significantly elongated [1,2]. But if the last parameter is not comparable with the time required for the heat generated in the fuel elements to transport from a fuel to a coolant, feedback on the effect of changes in coolant parameters on reactivity during this time will not have time to manifest. Here was studied that the thermal constants of fuel elements can be shortened by using molybdenum as a structural material of fuel elements. Other aspects related to the use of molybdenum in nuclear reactors have also been studied. When performing the study the neutron-physical properties of isotopes of natural molybdenum (nuclear data library JENDL-4.0) and thermal properties of metallic molybdenum were used. The following results were obtained: 1. A method for reducing the thermal constant of fuel elements for light water and fast reactors by using dispersion fuel in cylindrical fuel rods containing, for example, granules of metallic U-Mo-alloy into Mo-matrix was proposed. 2. The necessity of molybdenum enrichment by weakly absorbing isotopes was shown. 3. Total use of isotopic molybdenum will be more than 50%. 4. Mo has a good corrosion resistance to Pb and Pb-Bi eutectic A decrease in thermal constants of fuel elements, in combination with an increase in the mean prompt neutron lifetimes in the absence of the heat transfer crisis in fast reactors, can be promising way for a better reactor operation safety even under the conditions of the prompt neutron excursions.